PENGARUH JENIS PELARUT DAN SENYAWA PENGEMBAN TERHADAP EFISIENSI PEMISAHAN LOGAM PERAK DENGAN TEKNIK MEMBRAN CAIR BERPENDUKUNG - Samsul Bahri; Yeti Kurniasih; Ahmadi Ahmadi (Universitas Pendidikan Mandalika Mataram, 2017)
Silver metal found in the metal plating industry wastewater, industrial process photography and X-ray film process. Wastes that still lack the metallic ions of silver if thrown in the water without further treatment would endanger the life of organisms, mainly bacteria, plants and living things, as silver metal is a metal that is toxic in dissolved form. One separation technique can be used with supported liquid membrane (SLM) technique. This study aimed to identify the type of solvent and carrier compound to percent transport of silver metal from the feed phase to phase receivers with SLM techniques. This type of research used in this study was an experimental research in the laboratory. Percent transport of metal ions Ag + with techniques SLM had done by varying the type of solvent was n-hexane, kerosene, toluene and chloroform to dissolve the compound carrier TBP and D2EHPA with each concentration 1 M. The concentration of the metal ions Ag+ in phase receiver after separation techniques SLM was measured by Atomic Absorption Spectrophotometer (AAS) at a wavelength of 328.1 nm, then the calculated percent metal Ag+ ion transport. Based on the results showed that the percent of the silver metal transport centipede on the use of solvent n-hexane and chloroform, with transport by 33.9% percent. While the percent of the highest transport to the use of compounds that was using the carrier of carrier compound TBP, with transport by 33.9% percent.